Environmental management through public control - Valieva A.R. (BIO Web of Conferences)
One of the global challenges of our time is the environmental situation deterioration. The environmental management system is designed to ensure the order and consistency of solving environmental issues through approved methods, procedures, and processes. Public participation plays a special role in this process. The forms of public participation in environmental protection may vary. The article examines management process in natural resource management, the use of public control in the field of environmental safety, in particular, the development of the institute of public inspector for environmental protection in the Russian Federation. Meeting the necessary public need in the field of environmental safety requires bringing public control in the environmental field into a certain organized system with appropriate norms and rules. The paper analyzes the practical and legal foundations of public inspection, identifies a number of areas for improving the activities of environmental inspectors.